2013
DOI: 10.4236/aim.2013.31018
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Identification of Two Antibacterial Agents from <i>Chromolaena odorata</i> L. Active against Four Diarrheal Strains

Abstract: Chromolaena odorata L (Asteraceae) is a bad invasive plant, found in the humid tropics and sub-tropics worldwide. It is used against dysentery, diarrhea, malaria, wound healing, headache and toothache in traditional medicine. In the present study, we investigated the antibacterial activities of different leaves extracts of Chromolaena odorata L. (cyclohexane, dichloromethane, ethyl acetate and butanol) against four clinical diarrheal strains (Klebsiella oxytoca, Salmonella enterica, Shigella sonnei and Vibrio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 27 publications
0
19
0
1
Order By: Relevance
“…Common names are Siam weed, Christmas bush, and common floss flower (Chakraborty, Rambhade, & Patil, 2011;Queensland Department of Agriculture, Fisheries and Forestry, 2013). Previous studies have reported that this plant exhibits biological activities: antimicrobial activity (Suksamrarn et al, 2004;Pisutthanan et al, 2005;Vital & Rivera, 2009;Naidoo, Coopoosamy, & Naidoo, 2011;Sukanya, Sudisha, Prakash, & Fathima, 2011;Mondal, Bhargava, Shivapuri, & Kar, 2012;Atindehou et al, 2013;Eze, Oruche, Onuora, & Eze, 2013;Kigigha & Zige, 2013;Stanley, Ifeanyi, Nwakaego, & Esther, 2014); antibiofilm activity (Yahya, Ibrahim, Zawawi, & Hamid, 2014); antihepatotoxicity (Alisi, Onyeze, Ojiako, & Osuagwu, 2014;Asomugha, Okafor, Ijeh, Orisakwe, & Asomugha 2014); antimalarial activity (Pisutthanan et al, 2005); anthelmintic activity (Vital & Rivera, 2009); antiviral activity (Pisutthanan et al, 2005); phytopathogenic activity (Sukanya et al, 2009); antiprotozoal activity (Vital & Rivera, 2009); wound healing (Anyasor, Aina, Olushola, & Aniyikaye, 2011); and antioxidant activity (Akinmoladun, Ibukun, & Dan Ologe, 2007). Chemical compounds produced by this plant play a role in inhibiting the growth of pathogenic microorganisms: leaf extract contains coumarins, tannins, steroids, saponins, terpenoids, terpenes, flavonoids and cardiac glycosides (Phan et al, 2001;Akinmoladun et al, 2007;Vital & Rivera, 2009;Anyasor et al, 2011;Lavanya & Brahmaprakash, 2011); flower extract contains flavonoids (isosakuranetin, persicogenin, 5,6,7,4′-tetramethoxyflavanone and 4′-hydroxy-5,6,7-trimethoxyflavanone) and flavones (acacetin and luteolin) (Suksamrarn et al, 2004); root extract contains triterpenes, poriferasterol, octadecane, butyrospermol acetate, bis(2-ethylhexyl) phthalate, chrysophanol and physcion…”
Section: Introductionmentioning
confidence: 99%
“…Common names are Siam weed, Christmas bush, and common floss flower (Chakraborty, Rambhade, & Patil, 2011;Queensland Department of Agriculture, Fisheries and Forestry, 2013). Previous studies have reported that this plant exhibits biological activities: antimicrobial activity (Suksamrarn et al, 2004;Pisutthanan et al, 2005;Vital & Rivera, 2009;Naidoo, Coopoosamy, & Naidoo, 2011;Sukanya, Sudisha, Prakash, & Fathima, 2011;Mondal, Bhargava, Shivapuri, & Kar, 2012;Atindehou et al, 2013;Eze, Oruche, Onuora, & Eze, 2013;Kigigha & Zige, 2013;Stanley, Ifeanyi, Nwakaego, & Esther, 2014); antibiofilm activity (Yahya, Ibrahim, Zawawi, & Hamid, 2014); antihepatotoxicity (Alisi, Onyeze, Ojiako, & Osuagwu, 2014;Asomugha, Okafor, Ijeh, Orisakwe, & Asomugha 2014); antimalarial activity (Pisutthanan et al, 2005); anthelmintic activity (Vital & Rivera, 2009); antiviral activity (Pisutthanan et al, 2005); phytopathogenic activity (Sukanya et al, 2009); antiprotozoal activity (Vital & Rivera, 2009); wound healing (Anyasor, Aina, Olushola, & Aniyikaye, 2011); and antioxidant activity (Akinmoladun, Ibukun, & Dan Ologe, 2007). Chemical compounds produced by this plant play a role in inhibiting the growth of pathogenic microorganisms: leaf extract contains coumarins, tannins, steroids, saponins, terpenoids, terpenes, flavonoids and cardiac glycosides (Phan et al, 2001;Akinmoladun et al, 2007;Vital & Rivera, 2009;Anyasor et al, 2011;Lavanya & Brahmaprakash, 2011); flower extract contains flavonoids (isosakuranetin, persicogenin, 5,6,7,4′-tetramethoxyflavanone and 4′-hydroxy-5,6,7-trimethoxyflavanone) and flavones (acacetin and luteolin) (Suksamrarn et al, 2004); root extract contains triterpenes, poriferasterol, octadecane, butyrospermol acetate, bis(2-ethylhexyl) phthalate, chrysophanol and physcion…”
Section: Introductionmentioning
confidence: 99%
“…Research carried out in China showed resistance of Shigella to multiple antibiotics such as aztreonam (30.8%), ampicillin (92.3%), gentamicin (53.8%), piperacillin (61.5%), ceftazidime (30.8%), cefotaxime (30.8%) and ampicillin (92.3%). The screening of medicinal plants such as C. odorata for new bioactive agents against bacteria is promising as the species is effective against some bacteria such as S. faecalis, P. aeruginosa (Irobi, 1992), S. typhi and E. coli (Zige et al, 2013), B. subtilis, B. cereus, S. aureus, S. epidermidis and E. coli (Naidoo et al, 2011;Sukanya et al, 2011) as well as V. cholerae (Atindehou et al, 2013).…”
Section: Semi-systematic Namementioning
confidence: 98%
“…Reports have shown that C. odorata exhibited anti-bacterial activity against opportunistic human pathogens (Irobi, 1992;Caceres et al, 1995). Atindehou et al (2013) tested cyclohexane, dichloromethane, ethyl acetate and butanol extracts of C. odorata leaves for their antibacterial activity against four bacteria that cause intestinal tract infection, namely Klebsiella oxytoca, Salmonella enterica, Shigella sonnei and Vibro cholerae isolated from patients confirmed to have diarrhoea in France. The display of anti-bacterial activity in terms of minimum inhibition concentration (MIC) values ranged from 0.15 to 1.2 mg/ml.…”
Section: Semi-systematic Namementioning
confidence: 99%
“…Kingdom: Plantae Subkingdom: Viridiplantae Infrakingdom: Streptophyta Superdivision: Embryophyta Division: Tracheophyta Subdivision: Spermatophytina Class: Magnoliopsida Asian J Pharm Clin Res, Vol 11, Issue 10, 2018, [34][35][36][37][38] Superorder: Asteranae Order: Asterales Family: Asteraceae Genus: Chromolaena Species: C. odorata. Nomenclature C. odorata aka Eupatorium odoratum is a weedy herb native of Central and South America, which has spread throughout the tropical and subtropical areas [9,10].…”
Section: Taxonomical Classification [8]mentioning
confidence: 99%
“…From literature review regarding the traditional uses, phytochemical properties of C. odorata are antibacterial [28][29][30][31], anticancer [32], anticonvulsant [33], antidiabetic [34][35][36], antidiarrheal [37,38], antifungal [39,40], anti-inflammatory [41][42][43], antioxidant [44][45][46][47], and antiparasitic [24], hemostatic and wound healing [47,48], and hepatoprotective activities [49,50].…”
Section: Traditional Usesmentioning
confidence: 99%